Daily Management of Patients on Multikinase Inhibitors’ Treatment - Colombo, Carla; De Leo, Simone; Trevisan, Matteo; Giancola, Noemi; Scaltrito, Anna; Fugazzola, Laura (Frontiers in Oncology, 2022)
In a minority of differentiated TC cases and in a large percentage of poorly differentiated TCs (PDTCs) and anaplastic TCs (ATCs) the prognosis is poor due to the lack of response to conventional treatments. In the last two decades, multi-kinase inhibitor (MKI) compounds have been developed and demonstrated to be very effective in these aggressive cases. Besides the great efficacy, several adverse events (AE) have been reported in virtually all patients treated with MKIs, largely overlapping between different compounds and including hypertension, diarrhoea, anorexia, decreased weight, fatigue, and proteinuria. Most grade 3 to 4 adverse reactions occur during the first 6 months of treatment and require dosage reduction and/or drug discontinuation. Due to severity of the AEs related to the treatment with MKIs, a multidisciplinary team is definitely required for the daily management of these patients, for the evaluation of the disease status and the psychophysical condition. Moreover, it is crucial that the patients could have a facilitated access to reach either specialist doctors or nurses who must have been trained to follow them for their individual clinical complications. The follow-up visits should take place at monthly intervals until the 6th month and then every 1-2 months until the completion of the 1st year of treatment. The flow chart followed at our tertiary Center is reported in the present Review as a real-life-based example for the follow up of patients with advanced TC on MKIs treatment.